Business Strategy Formulation of Sharia Rural Bank (SRB) in Facing Pandemic - Ningky Sasanti Munir (University of Darussalam Gontor, 2022)
This study was conducted to formulate a business strategy for a sharia rural bank whose performance has decreased because the financing sector served is affected by Covid-19. This study is applied research that is qualitative and uses a single case study approach. Primary data was obtained through interviews with several members of the board of commissioners, members of the board of directors, and heads of divisions. Secondary data were obtained from internal company documents, while external sources were mostly from regulatory bodies for the sharia banking industry in Indonesia. A framework from David et al. (2020) is used to obtain a business strategy formulation. For the upcoming three years, the business strategy that should be carried out are market penetration and product development, i.e., conducting selective increase in financing in prospective sectors, conducting coaching in the micro and small sectors so that they can better cope with the impact of Covid-19, and developing products for first-time young customers.